(untitled) (Archive of Conferences, 2020)
Translation into the student’s native or first language is unnecessary in many cases when teaching English vocabulary to speakers of other languages. For many years traditional linguists have advocated translating all new vocabulary into the student’s native language before he or she is ready to read or speak an unfamiliar passage.